Prediction of the evolution of the aortic diameter according to the thrombus signal from MR images on small abdominal aortic aneurysms - Karyati, C. M; Lalande, A; Steinmetz, E; Mutiara, A; Brunotte, F (Medical and Health Science Journal, 2011)
We have studied T1 and T2 weighted MR images of thrombus from examination of patients with small abdominal aortic aneurysms in order to know whether the thrombus signal can be linked with the aortic diameter enlargement, and then could predict rupture risk of the aorta wall. Data were obtained from 16 patients with Small Abdominal Aortic Aneurysms (SAAA) who had been examined since July 2006 to January 2010 with MR Images. Several parameters were used to study the thrombus signal, such as mean, median, standard deviation, skewness and kurtosis. Each parameter was calculated for the thrombus area, and the signal in the muscle was used to normalize the mean, median and standard deviation of signal in thrombus. After then, those parameters were compared with evolution of the aortic diameter. 13 of the 16 patient with SAAA had a thrombus. Unfortunately there were no correlations between thrombus signals with the evolution of the aortic diameter (R often less then 0.3). But some parameter show links between thrombus signal and maximum diameter (mean (R=0.318)), median (R=0.318), skewness (R=0.304)) or with D maximum diameter (mean (R=0.512)). We cannot use thrombus signal alone as the parameter to predict the evolution of the aortic diameter. This study is the first step of our overall study. In the next step, we will use blood flow velocity with 3D/4D modelisation on the aortic aneurysm as a comparison parameter for predicting the rupture risk of the aortic wall. Moreover, relationship between flow data and thrombus will be studied.
Keywords: aortální aneurysma; difuzní magnetická rezonance; Signal Transduction; Magnetic Resonance Imaging; Humans; trombóza; lidé; signální transdukce; Aortic Aneurysm; magnetická rezonanční tomografie; Aorta, Abdominal; aorta abdominalis; Diffusion Magnetic Resonance Imaging; Thrombosis